EFFECT OF CHEMICAL TREATMENT WITH OXIDANTS ON THE MECHANICAL PROPERTIES OF LUFFA SPONGE/UNSATURATED POLYESTER COMPOSITES - NOURI LAIB; AZZEDINE BENYAHIA; ALI REDJEM; NADIR DEGHFEL (Université de M'sila, 2020)
This study investigates a synergistic treatment comprising alkali, permanganate, dichromate, silane and bleaching pretreatment on Luffa sponge (LF) fibers intended to be used as reinforcement in an unsaturated polyester (UP) matrix to improve the mechanical properties of Luffa sponge fibers reinforced unsaturated polyester composites. Treatment effects by NaOH (5 wt%), K2Cr2O7 (0.2 wt%), KMnO4 (0.0125 wt%), NaClO (13°) and silane (0.5 wt%) on the performance of the prepared composites were evaluated by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), SEM and mechanical tests (flexural strength and modulus). The results of the analyses indicated that composites reinforced with treated fibers have higher flexural strength than composites reinforced with untreated fibers
Keywords: Luffa fiber, composite, alkali treatment, flexural strength